(untitled) (Research, Society and Development, 2021)
The highest prevalence of enteroparasitosis occurs in developing countries and is a major public health problem. These infections are common during childhood, however, other age groups are not exempt, since the transmission of the disease is closely related to the health and hygiene conditions of individuals. The present study sought to analyze in the scientific literature, the factors associated with the prevalence of enteroparasitosis in the elderly in Brazil. This is a retrospective research, with a literary review based on publications indexed in the BVS, SciELO, Google Scholar databases. Search descriptors used the terms "parasitosis" and "elderly" and "prevalence". As inclusion criteria, research published between 2000 and 2020, complete and free texts, was considered. As exclusion criteria, studies in other countries, dissertations and monographs were disregarded. The results found demonstrated a high prevalence of enteroparasitosis in the elderly in Brazil, in addition to identifying several factors attributed to the predisposition to these intestinal parasitic diseases, especially regarding hygiene and basic sanitation habits. Despite detecting some phenomena such as, the hygienic-hygienic conditions that can occur the presence of parasitism in the elderly, it was also observed that no factor absolutely determines positivity in the elderly population.